Sp1-Induced lncRNA Rmrp Promotes Mesangial Cell Proliferation and Fibrosis in Diabetic Nephropathy by Modulating the miR-1a-3p/JunD Pathway - Yang, Hansen; Wang, Jia; Zhang, Zheng; Peng, Rui; Lv, Dan; Liu, Handeng; Sun, Yan (Frontiers in Endocrinology, 2021)
Diabetic nephropathy (DN) is a serious complication of diabetes mellitus. Long non-coding RNAs (lncRNAs) are regulators in DN progression. However, the regulatory mechanisms of multiple lncRNAs in DN remain to be determined. Our aim was to investigate the function and molecular mechanism of lncRNA RNA component of mitochondrial RNAase P (Rmrp) in DN. Here, we observed that the expression of Rmrp was up-regulated in the kidney of db/db DN mice and high glucose induced glomerular mesangial cells (MC). More importantly, the abnormal transcription of Rmrp was induced by nuclear transcription factor Sp1, which promotes the proliferation and production of fibrotic markers in MC. Subsequently, we screened the miRNAs related to Rmrp and found that Rmrp and miR-1a-3p are co-localized at the subcellular level of MC, and Rmrp could directly binds to miR-1a-3p. Further mechanism research demonstrated that the elevated miR-1a-3p significantly attenuated the proliferation and fibrosis-promoting effects induced by up-regulation of Rmrp. At the same time, we also investigated that miR-1a-3p can directly bind to Jun D proto-oncogene (JunD), thereby regulating the protein level of JunD. Rmrp-induced proliferation and fibrogenesis were reversed by co-transfection with JunD siRNA. In summary, Sp1 induced lncRNA Rmrp could drive the expression of JunD via sponging miR-1a-3p in DN progression.